PENERAPAN METODE LAPS HEURISTIC BERBANTUAN MEDIA DOMIKA PADA OPERASI BILANGAN BULAT DI SMP 18 MAARIF IBROHIMI - Aini, Sri Astutik Nur; Al 'Ayubi, Sholahudin; Siskawati, Fury Styo (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This research aims to find out how the application of the Laps Heuristic method assisted by the domino mathematics media (DOMIKA) can improve students’ learning outcomes in the subject of integers of class VII students of SMP 18 Ma'arif Ibrohimi. This research is classified as classroom action research with a qualitative approach. Based on the results of the study, the percentage of students’ activities in the first cycle was 69.14% and the second cycle was 80.53%. Meanwhile, the students’ learning outcomes in the first cycle were 35.3% and the second cycle was 94.1%. This proves that the activities and students’ learning outcomes can be improved by applying the Laps Heuristic method aided by domino mathematics media (DOMIKA). Keywords: Laps Heuristic, Domika, Learning Outcomes.